THE INFLUENCE OF IMPULSE BUYING TOWARD CONSUMER STORE LOYALTY AT HYPERMARKET IN JAKARTA - Soeseno Bong (Universitas Trisakti, 2010)
The rapid growth of the world economy driven by globalization and well supported by information technology results in economic boom across all the business throughout the world virtually leading to significant cross border transactions. The distribution and trading business in particular has no protection in the emerging countries like Indonesia. Hypermarket is one of the very popular concepts in distribution industry which has been developing rapidly in Indonesia and other emerging markets.The sustainable growth of Hypermarket industry largely attributed to consumers’ loyalty driven by marketing strategies and tactics supported by advanced information technology networking. Understanding Consumer behavior is one of the key successes of maintaining consumer loyalty. In this research, Consumer Impulse Buying Behavior and its influence on consumer loyalty has been dealt in detail. The main objective of this study was identifying the influence of Personal Antecedents, In-store Stimuli, In-store Browsing, Shopping Enjoyment, Convenience Orientation, and Perceived Time Pressure to Consumer Impulse Buying Behavior of Hypermarket in Jakarta to assess whether Impulse Buying influence the Consumer Store Loyalty. A conceptual model has been developed to test the relationships among these constructs. The findings expected to enrich the local traditional markets or small and medium enterprises to equip themselves as their competitive edge against the modern retailers and the hypermarkets as well. A new structural model devised to explain the various influences of the relationship among the variables. From the proposed seven hypotheses, there were four hypotheses significantly supportive, while three hypotheses were not supportive. Results and analysis show an interesting hypermarket consumer behavior in Jakarta which consistently enjoy shopping despite having time pressure, insufficient cash availability and lack of attention to in-store stimuli and store convenience. Interestingly this consumer segment was very impulsive in buying decisions and the empirical analysis shows that they were loyal to the store they visit to enjoy shopping as a simple means of recreation